Effect of interval and continuous small-sided games training on the bio-motor abilities of young soccer players: a comparative study - Daryanoosh, F.; Alishavandi, H.; Nemati, J.; Basereh, A.; Jowhari, A.; Asad-manesh, E.; Oliveira, R.; Brito, J. P.; Prieto-González, P.; García-Calvo, T.; Khoramipour, K.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Objective The present study compared the effects of two different small-sided game (SSG) training methods, interval (ISSG) and continuous (CSSG) on the bio-motor abilities of young soccer players.